2020
DOI: 10.1021/acs.jpcc.0c00175
|View full text |Cite
|
Sign up to set email alerts
|

Free Energy and Dynamics of Organic-Coated Water Droplet Coalescence

Abstract: Organic matter is prevalent in the atmosphere. How such organic matter affects droplet coalescence is a critical issue in atmospheric sciences. In this paper, we investigated the effects of three different organic coatings formed by benzoic acid, heptanoic acid, and pimelic acid on coalescence. We studied the thermodynamics of coalescence by calculating the free energy change and decomposed it into energetic ΔU and entropic TΔS contributions to understand the molecular details. ΔU was primarily determined by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 86 publications
0
22
0
Order By: Relevance
“…26 The free energy profiles suggested that the coalescence was spontaneous or energetically preferable for water droplets with and without coated materials. 25,26 These free energy calculations were carried out on water droplets in the atmosphere. 25,26 Sicard et al investigated the water droplets in an organic solvent (decane) with interfacially adsorbed nanoparticles by using dissipative particle dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The free energy profiles suggested that the coalescence was spontaneous or energetically preferable for water droplets with and without coated materials. 25,26 These free energy calculations were carried out on water droplets in the atmosphere. 25,26 Sicard et al investigated the water droplets in an organic solvent (decane) with interfacially adsorbed nanoparticles by using dissipative particle dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 These free energy calculations were carried out on water droplets in the atmosphere. 25,26 Sicard et al investigated the water droplets in an organic solvent (decane) with interfacially adsorbed nanoparticles by using dissipative particle dynamics. 15 The free energy profiles indicated that the nanoparticles reduced the fragmentation free energy during the breakup of water nanodroplets, facilitating emulsification.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in droplet size via evaporation or condensation can affect the chemical reactions that take place at the surface via changes in the relative dimensions and chemical environments of the interface and associated bulk phases (Prisle et al, 2012;Djikaev and Ruckenstein, 2019;Petters et al, 2020). The presence of surface-active organic molecules on droplet surfaces can also affect droplet surface tension (Shulman et al, 1996;Prisle et al, 2010b;Bzdek et al, 2020) and morphology (Kwamena et al, 2010) that affect both warm (Sareen et al, 2013;Ovadnevaite et al, 2017) and ice cloud nucleation (Knopf and Forrester, 2011;Perkins et al, 2020) as well as droplet coalescence (Pak et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of the Co 13 @Au 42 configurations obtained at these global minima are shown in Figure . It is interesting to note that the general shape of this FEPs resembles those observed in the coalescence of a water droplet. , …”
Section: Resultsmentioning
confidence: 61%
“…It is interesting to note that the general shape of this FEPs resembles those observed in the coalescence of a water droplet. 75,76 By looking at Figure 4, it can be noticed that for the FEPs above 1000 K, the free-energy difference between the global minimum and the separated NPs configurations decreases progressively. Moreover, the plateau at large values of dCM CoAu starts to disappear and is not noticeable below 1500 K. This phenomenon can be understood if we consider that precisely at 1000 K there is a change in the temperature regime as defined above, namely, from regimes 3 and 4.…”
Section: ■ Methodsmentioning
confidence: 99%